Echocardiographic Assessment of Left Ventricular Geometric Patterns in Hypertensive Patients in Nigeria - Adebayo, Rasaaq A. (Libertas Academica, 2013)
Left ventricular (LV) hypertrophy is an important predictor of morbidity and mortality in hypertensive patients, and its geometric pattern is a useful determinant of severity and prognosis of heart disease. Studies on LV geometric pattern involving large number of Nigerian hypertensive patients are limited. We examined the LV geometric pattern in hypertensive patients seen in our echocardiographic laboratory. A two-dimensional, pulsed, continuous and color flow Doppler echocardiographic evaluation of 1020 consecutive hypertensive patients aged between 18 and 91 years was conducted over an 8-year period. LV geometric patterns were determined using the relationship between the relative wall thickness and LV mass index. Four patterns of LV geometry were found: 237 (23.2%) patients had concentric hypertrophy, 109 (10.7%) had eccentric hypertrophy, 488 (47.8%) had concentric remodeling, and 186 (18.2%) had normal geometry. Patients with concentric hypertrophy were significantly older in age, and had significantly higher systolic blood pressure (BP), diastolic BP, and pulse pressure than those with normal geometry. Systolic function index in patients with eccentric hypertrophy was significantly lower than in other geometric patterns. Doppler echocardiographic parameters showed some diastolic dysfunction in hypertensive patients with abnormal LV geometry. Concentric remodeling was the most common LV geometric pattern observed in our hypertensive patients, followed by concentric hypertrophy and eccentric hypertrophy. Patients with concentric hypertrophy were older than those with other geometric patterns. LV systolic function was significantly lower in patients with eccentric hypertrophy and some degree of diastolic dysfunction were present in patients with abnormal LV geometry.